Plan de negocios para la comercialización de vino frutal, en tiendas de conveniencia Atimasa y Nucopsa de la ciudad de Guayaquil, para el año 2019. - Bourne Macías, Jimmy Federico (2019)
Property LA JIMAGUA, belonging to the micro-enterprise segment, is dedicated to the elaboration of artisan products such as smoked ham. Since the year 2017 its owner decides to venture into the production of alcoholic beverages, getting to develop a natural apple wine without sulfites or preservatives that is baptized as GUAJIRO, named in honor of the cuban peasant. Through a marketing plan, it is sought to position it among the consumers' favorites, using convenience stores as an indirect channel, which, thanks to its security and 24/7 format, become a destination and preferred sites for many customers. Applying available methodologies of market study to then tabulate and analyze the information, it is concluded that there is a little covered demand in the category of fruit wines in general. Considering the current production capacity of the property and the calculated demand, it is routed the project to the city of Guayaquil with store to store attention under horizontal coverage, in this way it can cover the needs of consumers efficiently. When projecting sales and financial flows, it is sought to reach the maximum goal that is to double the sales and profits of the owner, as well as generate new sources of employment.